Teaching Video NeuroImages: Minimal anomalies of dorsal midbrain syndrome (Parinaud syndrome). (3rd January 2017) - Rojas, Pilar; Maeder, Philippe; Borruat, François-Xavier
Abstract : Parinaud syndrome results from posterior commissure dysfunction, and is associated with 4 major signs: limitation of upgaze, pupillary light-near dissociation, convergence abnormalities, and Collier sign. 1, 2